Mechanical Injury Predominates in Rural Bali, Indonesia: Implications for Prevention and Treatment of Ocular Trauma - Kadek Dwi Pradnya Andrastea; Ni Made Lienderiwati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Ocular trauma constitutes a significant global health concern, leading to preventable visual impairment and blindness. This study delves into the clinical characteristics of ocular trauma in Karangasem Regency, Bali, Indonesia, with an emphasis on the prevalence of mechanical injuries and their subsequent implications for preventive measures and treatment strategies. Methods: A retrospective observational study was conducted using medical records of patients diagnosed with ocular trauma at two hospitals in Karangasem Regency from January to December 2023. Data collected included demographics, type of trauma, cause of injury, onset, treatment, complications, and visual acuity. Results: The study encompassed 385 patients (392 eyes) with ocular trauma. The majority of patients were male (78.7%), resided in rural areas (77.4%), and were adults aged 19-44 years (46.49%). Mechanical injury was the most prevalent type (45.15%), with closed-globe injuries accounting for 43.62% and open-globe injuries accounting for 1.53%. The leading causes of trauma were foreign bodies (44.13%) and blunt injury (27.04%). Notably, only 52.31% of patients sought medical attention within 24 hours of injury. The most frequent complications included subconjunctival bleeding (20.4%), corneal erosion (15.5%), and palpebral rupture (8.9%). Conclusion: Mechanical injury is the predominant type of ocular trauma in rural Bali, primarily affecting adult males involved in labor-intensive occupations. The delayed presentation for treatment underscores the need for heightened awareness and improved access to healthcare services. These findings emphasize the importance of targeted prevention programs and prompt management of mechanical eye injuries to reduce the burden of ocular trauma in rural Indonesia.